Implementing a knowledge management system in an academic institution: Issues and challenges - Din, Inson; Abang Ibrahim, Dayang Hanani (2005)
Today as we are heading to competitive environment, the nature and significance of knowledge is changing rapidly.This environment has made the role of knowledge greater and more crucial than ever before. The changing importance of knowledge had encouraged companies and organizations to invest time and money for implementing knowledge management system. Academic institutions are no exception.This paper describes the transition of applying knowledge management concept in an academic institution that is UNIMAS. Issues covered include developing knowledge sharing culture, challenges faced by the group in implementing the system and solutions, and lessons learned and tips that could be shared to other related organizations/institutions.Among all, it describe major issues regarding people, hardware, software, technology and organizational politic.